Sosialisasi Pengenalan Sejarah Lokal dalam Upaya Menumbuhkan Minat Sejarah di MA Muhajirin Tugumulyo Kabupaten Musi Rawas - Ratna Wulan Sari (Pemberdayaan Masyarakat : Jurnal Aksi Sosial, 2024)
Education and local wisdom in the era of global perspective is how the role of a teacher in guiding students without leaving the values of local wisdom that exist in society. In learning at school, especially history lessons, there should be an introduction to local history in Musi Rawas Regency. The history education internal community partnership program aims to socialize the introduction of Local History in an effort to foster historical interest in MA MuhajirinTugumulyo, Musi Rawas Regency The importance of socializing the introduction of local history is to increase the knowledge and experience of both learning students and teachers at MA Muhajirin Tugumulyo, Musi Rawas Regency. The service team has an obligation to provide socialization in the field of history so that it can be useful for the development of science and technology in society. The field of history does not only talk about the past but the advancement of science and technology can be utilized as the main source through the elaboration of local history around the community. This community service activity is expected to be able to contribute both teachers and students at MA Muhajirin Tugumulyo, Musi Rawas Regency. The implementation of this community service was carried out at MA Muhajirin Tugumulyo, Musi Rawas Regency as a form of team attention in the field of history to maintain the existence of local history, especially for the younger generation. This service uses an implementation method in the form of steps to be taken in providing training through the stages of material preparation, activity implementation, and activity evaluation stages.